Hildegard E. Peplau in model medosebnih odnosov - Ramšak-Pajk, Jožica (Obzornik zdravstvene nege, 2000)
The first part of the article shortly introduces Hildegard Peplau and defines her theory of interpersonal relations between nurse and patient. The four phases of the theory and the different roles, which the nurse takes through them, are described. In conclusion the article discusses the possibility of the application of the model of interpersonal relations to the nursing process. The conclusion emphasizes the value of the use of the mentioned modeland effective communication between nurse and patient.
Keywords: Interpersonal relations; medosebni odnosi; Nurse-patient relations; Nursing care; zdravstvena nega